Validity and Practicality of Geogebra Application-Based Mathematics Learning Tools to Train Visual-Spatial Intelligence - Hikmah, Rezkiyana (JDIME: Journal of Development and Innovation in Mathematics Education, 2023)
An effective distance learning tool must be able to train students' spatial intelligence to help them develop visualization skills. Thus, this study aims to see the validity and practicality of GeoGebra application-based distance learning tools. This development research (R&D) uses a three-phase development approach based on Plomp Theory, which is divided into three stages: preliminary research, prototyping, and assessment. Validation and practicality questionnaires were used to obtain research data and analyzed with descriptive qualitative statistics. The results of the data analysis showed that the mathematics learning tools were evaluated with the "Very Valid" category. This is based on the assessment of three validators where the total average value of the validity of the lesson plan is 4.28 which is included in the "very valid" category, while the total average value of the validity of the LKPD is 4.24 which is also included in the category. In addition, the LKPD and lesson plans developed were also considered "practical". This is based on the assessment of three validators who produced an average final value of the RPP's practicality of 85, which is included in the "A" category, which means that the RPP that serves as a learning device can be used without modification, and the overall average value of the LKPD's practicality is 84.57, which puts it in the "B" category, which indicates that the LKPD can be used as a learning device with minor modifications.  This means that Geogebra-based learning tools are reliable tools to assist teachers in developing learners' mathematical and spatial visualization skills.